2022
DOI: 10.1002/mabi.202200236
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinted Hydroxyapatite or Graphene Oxide Containing Nanocellulose‐Based Scaffolds for Bone Regeneration

Abstract: Bone tissue is usually damaged after big traumas, tumors, and increasing aging-related diseases such as osteoporosis and osteoarthritis. Current treatments are based on implanting grafts, which are shown to have several inconveniences. In this regard, tissue engineering through the 3D bioprinting technique has arisen to manufacture structures that would be a feasible therapeutic option for bone regenerative medicine. In this study, nanocellulose-alginate (NC-Alg)-based bioink is improved by adding two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In addition, it can be chemically modified and has been widely used for biomedical applications in the last few years. 44 Incorporating GO with gelatin matrix can improve their mechanical properties and creates additional pore structures for better diffusion of nutrients and waste products. 26 Due to the excellent biocompatibility and robust physical properties, the combination formulation of gelatin and GO presents a viable choice for the fabrication of wound dressing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can be chemically modified and has been widely used for biomedical applications in the last few years. 44 Incorporating GO with gelatin matrix can improve their mechanical properties and creates additional pore structures for better diffusion of nutrients and waste products. 26 Due to the excellent biocompatibility and robust physical properties, the combination formulation of gelatin and GO presents a viable choice for the fabrication of wound dressing.…”
Section: Discussionmentioning
confidence: 99%
“…Creating a HAp-based composition of the scaffolds with polymers improves the mechanical properties and enables the production of multilayer compositions for 3D printing [14,[54][55][56]58]. To increase the mechanical properties of 3D-printed HAp/polymeric biomaterials, in some research, graphene oxide was added [57].…”
Section: Status Of Calcium Phosphate Biomaterials In 3d (Bio)printing...mentioning
confidence: 99%
“…Notably, compared to the prior study, the use of allograft bone particles was found to contribute to enhanced cell viability during and after printing, for 90% viability for up to 28 days in vitro. Moreover, the potential for graphene oxide additives to improve bioink mechanical properties was explored in several applications with alginate- [149], gelatin- [150], alginate/gelatin blend-, and gellan gum-based hydrogels [151]. Generally, the addition of graphene oxide was found to contribute mechanical strength and improve the bioink printing performance, and in several applications, was tuned in accordance with the hydrogel with chemical modifications to function in targeted drug delivery and tumor suppression.…”
Section: Nanomaterials Composites For Bone Bioprintingmentioning
confidence: 99%